2020
DOI: 10.3390/app10030977
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solid Particle Erosion on Helicopter Rotor Blades Surfaces

Abstract: In this study, titanium alloy (Ti-4Al-1.5Mn), magnesium alloy (Mg-Li9-A3-Zn3), or aluminum alloy (Al7075-T6) were used to construct the shell model of helicopter rotor blade to study the solid particle erosion of helicopter rotor blades. The erosion resistance of the three materials at different angles of attack (6°, 3°, or 0°) and particle collision speeds (70, 150, or 220 m/s) was examined using the finite volume method, the discrete phase method, and erosion models. In addition, the leading edge of the heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The most likely explanation of the process seems to be the existence of forces acting perpendicular to the surface. With aluminium, a ductile material, we see both wear due to repeated deformation (work hardening, followed by surface cracking) which explains the erosion occurring at typical angles of incidence, and we also see cutting wear as described by Finnie [30,53]. Cutting wear is produced by forces working in the surface of the material.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…The most likely explanation of the process seems to be the existence of forces acting perpendicular to the surface. With aluminium, a ductile material, we see both wear due to repeated deformation (work hardening, followed by surface cracking) which explains the erosion occurring at typical angles of incidence, and we also see cutting wear as described by Finnie [30,53]. Cutting wear is produced by forces working in the surface of the material.…”
mentioning
confidence: 69%
“…The firstgeneration of these coatings was fabricated from single phase metal nitrides (e.g., TiN). However, it was found that the added layer did not perform as expected for the normal angle as a result of its high internal stress and low toughness [30][31][32]. This obstacle was afterwards resolved by using the second generation of ERC, which consists of multi-layered structures of metal/ceramic, where the crack generated by the SPE on the exposed surface layer is blocked by the layer that follows it.…”
Section: Foreign Object Damagementioning
confidence: 99%
See 3 more Smart Citations